Phytochemistry, Ethnomedicine and Pharmacology of Jatropha gossypiifolia L: A Review - , Omolola Temitope Fatokun; , Omorogbe Liberty; , Kevwe Benefit Esievo; , Samuel Ehiabhi Okhale; , Oluyemisi Folashade Kunle (Archives of Current Research International, 2016)
Jatropha gossypiifolia L. [Euphorbiaceae], widely known as “bellyache bush”, is a medicinal plant native to Mexico, south America, India and commonly found in many west African countries such as Nigeria. Folkloric uses of the different parts of this plant in the tropics for the management of various diseases are enormous. Information was sourced from Hinari, JSTOR, PubMed, Medline, African Journals Online, Google Scholar, SCOPUS, and by reviewing the references of relevant literature. More recent studies showed the use of juice and extract of the plant in the management of sickle cell anaemia and the effect of its extracts on the reproductive system. Pharmacological studies have demonstrated significant action of different extracts and isolated compounds as haemostatic, anticholinesterase, antimicrobial, antiinflammatory, antidiarrheal, antihypertensive, and antiproliferative agents, among others, supporting some of its folkloric uses. The major secondary metabolites isolated from various extracts are terpenes-essential oils, alkaloids and coumarin - lignans. This review aims to provide an up to date overview of the phytochemistry, ethnomedicinal and pharmacological activities of J. gossypiifolia while providing an insight for future research towards both ethno pharmacological validation of its popular uses and its exploration as a new source of herbal medicinal products.